1984
DOI: 10.1111/j.1600-0528.1984.tb01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries in a group of adult Vietnamese refugees in Norway

Abstract: About 3500 Vietnamese refugees have settled in Norway since 1975. The purpose of this survey was to investigate the dental health of 200 Vietnamese refugees, 142 males and 58 females above the age of 12 years. The clinical examinations were done 3 weeks after arrival in Norway and included decayed, extracted and filled surfaces and teeth (DMFS and DMFT). The sample was divided into four age groups, 12-19, 20-29, 30-39 and 40+. Only 9% of the sample was cariesfree. Mean DMFT ranged from 8.7 in the youngest age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
4
9
1
Order By: Relevance
“…35 However, this study's findings were closer to the relatively more recent studies of permanent dentition of Vietnamese refugees living in Norway and Vietnamese living in refugee camps in Malaysia. 12,16 Although data were reported on dissimilar age groups and probably different social and ethnic backgrounds, which made comparisons difficult, both tended to support this study's findings on the prevalence of dental caries. 13 However, a common observation was the decayed component as the larger component of the DMFS indexes, while the filled component was lowest.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…35 However, this study's findings were closer to the relatively more recent studies of permanent dentition of Vietnamese refugees living in Norway and Vietnamese living in refugee camps in Malaysia. 12,16 Although data were reported on dissimilar age groups and probably different social and ethnic backgrounds, which made comparisons difficult, both tended to support this study's findings on the prevalence of dental caries. 13 However, a common observation was the decayed component as the larger component of the DMFS indexes, while the filled component was lowest.…”
Section: Discussionsupporting
confidence: 73%
“…13 However, a common observation was the decayed component as the larger component of the DMFS indexes, while the filled component was lowest. 12,16 This observation contradicted current findings, where the decayed component was generally the smallest.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Similar findings have also been reported from Zambia and Nigeria [Westwater, 1977;Akpata and Jackson, 1978]. A more recent study among Vietnamese refugees (newly arrived) in Nor way revealed a similar caries pattern [Selikowitz, 1984], Since these studies were descriptive only, explana tions of the findings were not offered. However, illdefined genetic disorders [Akpata and Johnson, 1978] and state of nourishment during calcification of the molar teeth [Westwater, 1977] as well as the relative inaccessibility of the second molars by oral hygiene measures [Enwonwu, 1981] have been suggested as possible explanations.…”
supporting
confidence: 64%